2013
DOI: 10.1016/j.bone.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic hip fractures: Bisphosphonates sales and observed turning point in trend. A population-based retrospective study

Abstract: The aim is to examine the temporal trends of hip fracture incidence in Portugal by sex and age groups, and explore the relation with anti-osteoporotic medication.From the National Hospital Discharge Database, we selected from 1st January 2000 to 31st December 2008, 77,083 hospital admissions (77.4% women) caused by osteoporotic hip fractures (low energy, patients over 49 years-age), with diagnosis codes 820.x of ICD 9-CM. The 2001 Portuguese population was used as standard to calculate direct age-standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…A U-shape relation between BMD and SES was also found in Australia (women, over 18 years) -individuals living in the extreme categories of SES had lower Bone Mineral Density (BMD) [36] For women, the age interaction with SES was not so clear: older women from areas in the medium SES had lower risk compared to women from lower SES areas and we need further studies to understand if this pattern is related to risk factors such as obesity, physical activity, occupational work, etc; risk for women in the age group 70-74 years was similar in the three SES areas and this may be due to the fact that in Portugal the health guidelines for osteoporosis prevention are mainly focusing in women between 65-74 ages [37].…”
Section: Discussionmentioning
confidence: 99%
“…A U-shape relation between BMD and SES was also found in Australia (women, over 18 years) -individuals living in the extreme categories of SES had lower Bone Mineral Density (BMD) [36] For women, the age interaction with SES was not so clear: older women from areas in the medium SES had lower risk compared to women from lower SES areas and we need further studies to understand if this pattern is related to risk factors such as obesity, physical activity, occupational work, etc; risk for women in the age group 70-74 years was similar in the three SES areas and this may be due to the fact that in Portugal the health guidelines for osteoporosis prevention are mainly focusing in women between 65-74 ages [37].…”
Section: Discussionmentioning
confidence: 99%
“…We identified eligible papers for the following 14 countries: Austria 9 , Denmark 17 , Estonia 24 , Finland 7 , France 25 , Germany 12 , Italy 26 , the Netherlands 27 , Norway 28 , Portugal 29 , Spain 30 , Sweden 31 , Switzerland 18 , and the UK – England 32 . Series differed between countries in time span, periodicity and age groups considered, but no data imputation was conducted (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This decrease could be the result of one or several factors mentioned in other studies (medication, prevention, changes in risk factors or changes in the codification system) [16]. However, the most plausible reason for the different period effect for men and women has been discussed in a previous study with the same population [15] where we identified a relationship between the number of anti-osteoporotic medication sales with the pattern of age-standardised incidence rates in women-the target population of the prescriptions. The current results confirm the existence of period effects even after adjusting for age and cohort effects.…”
Section: Discussionmentioning
confidence: 90%
“…Following that year, a sharp decrease was observed compatible with an increase in sales of anti-osteoporotic medication packages. In men, no such pattern was identified [15]. However, alterations in the prevalence of risk factors such as nutrition, smoking, alcohol or obesity can also be seen as period effects [16].…”
Section: Introductionmentioning
confidence: 99%